Genomic and Phytochemical Diversity Across a Collection of Snake Melon Landraces - Tsolakidou, Maria Dimitra; Markou, Anastasia; Kyratzis, Angelos C.; Kotsiras, Anastasios; Delis, Costas; Mattas, Konstadinos; Katsiotis, Andreas; Nikoloudakis, Nikolaos (My University, 2025)
Snake melons have been present for a millennia, despite their present limited use, and host a large degree of genetic and phytochemical diversity. The current study evaluated the genomic and biochemical diversity of Snake melon landraces of Cypriot and Greek origin, revealing significant degrees of genetic and mineral/phytochemical variation. Landraces showed a high potential for improving nutritional quality and a possible contribution to stress resilience. Whole-genome analysis highlighted a high degree of SNPs, InDels, SVs, and CNVs, especially in genotypes like Atzouri and ARI001024, indicating that functional variants influence phenotypic/chemical diversity. Biochemical profiling demonstrated great differences in the concentration of pigments, antioxidants, and minerals, with ARI001024 and ARI00894 exhibiting elevated levels of nutrients/phytochemicals. Hierarchical clustering and PCA analyses established relationships among traits, and reinforced the concept that these genotypes may offer valuable genetic resources for breeding programs under climate-resilient production schemes, emphasizing the need for conservation and further genomic characterization.
Keywords: Cucumis melo; SNPs; carotenoids; chlorophyll; heirloom varieties; minerals